2011
DOI: 10.1186/1471-2369-12-30
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of CRP to prealbumin levels predict mortality in patients with hospital-acquired acute kidney injury

Abstract: BackgroundAnimal and human studies suggest that inflammation and malnutrition are common in acute kidney injury (AKI) patients. However, only a few studies reported CRP, a marker of inflammation, albumin, prealbumin and cholesterol, markers of nutritional status were associated with the prognosis of AKI patients. No study examined whether the combination of inflammatory and nutritional markers could predict the mortality of AKI patients.Methods155 patients with hospital-acquired AKI were recruited to this pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 31 publications
2
67
0
Order By: Relevance
“…A serious relationship between low cholesterol and prealbumin levels and acute renal failure has also been identified. 21,[33][34][35][36] In our study we found no statistically significant difference on cholesterol levels between AKI and non-AKI groups, but similar to literature we found a relationship with lower cholesterol level and mortality.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A serious relationship between low cholesterol and prealbumin levels and acute renal failure has also been identified. 21,[33][34][35][36] In our study we found no statistically significant difference on cholesterol levels between AKI and non-AKI groups, but similar to literature we found a relationship with lower cholesterol level and mortality.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our results different studies reported that a decrease in the levels of albumin and prealbumin associated with an increase in morbidity and mortality in the literature. [31][32][33] Some of the studies reported the relationship between the patients with renal insufficiency and higher morbidity and mortality. A serious relationship between low cholesterol and prealbumin levels and acute renal failure has also been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Weights are inconsistently available in the ICU. Biochemical indicators of nutrition such as serum albumin and prealbumin levels can be affected by the fluid status and are both negatively associated with acute phase reactants and thus negatively correlated with inflammation, which is often rampant in the ICU patient (30). Anthropometric measures are time-consuming and require specially trained individuals.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Accordingly, previous studies, primarily in multiorgan failure and chronic renal failure patients, have utilized ratios of CRP to TTR in an attempt to better understand nutritional changes in the setting of active inflammatory states. 32,33 We calculated a ratio of CRP to TTR for similar reasons, and found the combination of a high CRP and low TTR was a more sensitive indicator of 3-month outcome than either marker alone. Both the CRP:TTR ratio and negative NBAL levels remained independent predictors of poor outcome at 3 months in multivariate analysis, indicating the importance of inflammation-mediated protein energy malnutrition acutely after SAH.…”
mentioning
confidence: 99%